Las Islas Afortunadas de Juba II. Púnico-gaditanos y romano mauretanos en Canarias - Mederos Martín, Alfredo; Escribano Cobo, Gabriel (Gerión. Revista de Historia Antigua, 2002)
The aim of this work is a review of the expedition sent by Juba II to the South of Mauretania and the Canary Islands, ca. 19-10 B.C., presumably with authorization of Augustus and roman ships participation. After to be married with Cleopatra Selene, he attempted to establish the beginning of a new Hellenistic Ptolemaic-Mauretanian dynasty, heiress of Great Alexander and the egyptian Pharaohs. In this project, he explored the territories of the South of Mauretania because he was waiting to f ind near his new kingdom the origin of the Nile river. After exploring the Drâa river, the expedition visited the Canary Islands making economic resources mention that they could awake foreign interest, dates, honey, wax, rushes, although signif icantly are not cited the most important, gray amber, dragon blood, shells, orchil and purple haemastoma for dyes, or salt and f ish for the elaboration of garum. 1.